Palm oil deodorizer distillate as toughening agent in polylactide packaging films. Issue 6 (22nd April 2016) - Ruellan, Alexandre; Ducruet, Violette; Gratia, Audrey; Saelices Jimenez, Lidia; Guinault, Alain; Sollogoub, Cyrille; Chollet, Guillaume; Domenek, Sandra
Abstract : A used‐as‐shipped biobased and biodegradable by‐product of the palm oil refining increases polylactide (PLA) elongation at break up to 130% and allows film blowing without further additives. PLA blends are biodegradable and comply with legal norms of food contact materials. Abstract: Polylactide (PLA) is the most used biodegradable and biobased food packaging polymer for rigid containers and films. However, its low ductility is a hurdle for increasing its applications in flexible food packaging. A solution is the use of additives. Palm oil deodorizer distillate (PODC) is revealed to be an excellent additive promoting PLA ductility. PODC is a by‐product of vegetable oil refining, which is available in stable quality and in sufficient amounts. Amorphous PLA/PODC blends had an elongation at break of around 130% and that of semi‐crystalline blends was still around 55% compared to the initial 5% of neat PLA. At the same time the PLA rigidity and high glass transition temperatures were kept. PODC was also a very efficient processing aid, allowing for film blow extrusion. The blends were stable in properties during six months without exudation. They complied with legal norms of Food Contact Materials (EU 10/2011) and induced no sensorial alteration of packed food. Therefore PODC is a very interesting alternative to common plasticizers for the production of flexible PLA packaging films. © 2016 Society of Chemical Industry